HIGHER EDUCATION IN TERMS OF WAR IN UKRAINE: LEGAL AND SOCIAL DIMENSIONS - Stryhul, Maryna (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2025)
The article aims to summarize the main challenges faced by higher education in Ukraine in the context of the full-scale invasion of Ukraine by the Russian Federation and conduct a comprehensive theoretical study of the legal framework for security threats, the devastation of universities, compelled digital transformation, quality assurance under martial law, financial obstacles, and international assistance. Some universities were forced to relocate due to the hostilities; their buildings were damaged or destroyed, and the educational infrastructure has undergone significant changes, especially in the East and South of Ukraine. The research theme is extremely relevant in the context of Ukrainian society, as the education sphere is one of the most affected by the war in Ukraine, which has faced new challenges. Research methods: the main methods used in writing this article are content analysis (research using content analysis by MAXQDA24, Python, and Internet resources), comparative analysis, and a questionnaire survey (online survey using Google Forms). Results: the task is to conduct a comprehensive analysis, identify needs and trends, develop effective programs to support the system of higher education, and restore higher education institutions. Conducting sociological research is important for understanding the depth of social transformations, as sociological analysis is an important tool for making informed management decisions aimed at supporting Ukrainian society in the context of war and rebuilding the state. Discussion: this article examines the repercussions of Russia’s extensive military aggression against Ukraine on the higher education system from 2022 to 2025. Additionally, the article offers pragmatic recommendations for universities and public policy both during wartime and in the context of post-war recovery.